A Novel Antimicrobial Peptide Sparamosin26–54 From the Mud Crab Scylla paramamosain Showing Potent Antifungal Activity Against Cryptococcus neoformans - Chen, Yan-Chao; Yang, Ying; Zhang, Chang; Chen, Hui-Yun; Chen, Fangyi; Wang, Ke-Jian (Frontiers in Microbiology, 2021)
Due to the increasing prevalence of drug-resistant fungi and the limitations of current treatment strategies to fungal infections, exploration and development of new antifungal drugs or substituents are necessary. In the study, a novel antimicrobial peptide, named Sparamosin, was identified in the mud crab Scylla paramamosain, which contains a signal peptide of 22 amino acids and a mature peptide of 54 amino acids. The antimicrobial activity of its synthetic mature peptide and two truncated peptides (Sparamosin1-25 and Sparamosin26-54) were determined. The results showed that Sparamosin26-54 had the strongest activity against a variety of Gram-negative bacteria, Gram-positive bacteria and fungi, in particular had rapid fungicidal kinetics (killed 99% Cryptococcus neoformans within 10 min) and had potent anti-biofilm activity against C. neoformans, but had no cytotoxic effect on mammalian cells. The RNA-seq results showed that after Sparamosin26-54 treatment, the expression of genes involved in cell wall component biosynthesis, cell wall integrity signaling pathway, anti-oxidative stress, apoptosis and DNA repair were significantly up-regulated, indicating that Sparamosin26-54 might disrupt the cell wall of C. neoformans, causing oxidative stress, DNA damage and cell apoptosis. The underlying mechanism was further confirmed. Sparamosin26-54 could bind to several phospholipids in the cell membrane and effectively killed C. neoformans through disrupting the integrity of the cell wall and cell membrane observed by electron microscope and staining assay. In addition, it was found that the accumulation of reactive oxygen species (ROS) increased, the mitochondrial membrane potential (MMP) was disrupted, and DNA fragmentation was induced after Sparamosin26-54 treatment, which are all hallmarks of apoptosis. Taken together, Sparamosin26-54 has a good application prospect as an effective antimicrobial agent, especially for C. neoformans infections.